Anomalous thermal conductivity of La2-xSrxCuO4: Possibility of a polaronic glass - Nuñez Regueiro, M. (1987)
Fil: Nuñez Regueiro, M. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina